STUDY OF AN EFFECTIVE NON-TRACKING CONCENTRATED SOLAR POWER SYSTEM AS A VIABLE SOLAR THERMAL BIOMASS CONVERSION PROCESS - M. ZAHARI, M. SHAHRIR; ISMAIL, SHAHRUL; SRINIVASAN, THIRU MANGAI (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
Sunlight is a natural energy source and abundantly available but restricted to certain timeframe and angles depending on the Earth surface where it could be effectively harvest for energy source. Therefore, the purpose of the study is to evaluate the performance of fixed setting systems in comparison to a custom made non-tracking solar concentrator especially in their potential to reach suitable internal temperature ranges required for pyrolysis purpose within a sealed quartz glass reactor as the heat receiver. For the solar collector, six segmented mirrors were placed at varied angles to enable continuous sun ray directed toward one focal spot, at any time of the day without the need for electrical tracking or manually adjusting it based on the sun angle. The parameters in designing the system setup include: Focal Length, Tilt Angle of lens and Azimuth Angles. It is observed that by fixing the focal length to 35 cm and adjusting the tilt angle of the lens to be fixed at 30°, the reactor was able to achieve the desired temperature range of between 700 to 730. It can be concluded that the combination of Fresnel lens and simple mirror system were capable of concentrating sunlight into a specific area to reach the desired heating range without the need for complicated, costly equipments.